Pelatihan produksi bersih dan manajemen usaha kepada kelompok usaha garam rakyat di Gampong Kuala Idi Cut Kabupaten Aceh Timur (Clean production training and business management for the people's salt business group in Kuala Idi Cut Village, East Aceh District) - Iswahyudi, I; Muslimah, M; Abdurrachman, A (Universitas Syiah Kuala, 2021)
The purpose of this service activity was to provide a training in the clean production and business management to the people's salt business group in Kuala Idi Cut Village, Darul Aman Sub-District, East Aceh District. The procedure for implementing activities consists of the coordination of activities, socialization, a training, and mentoring. The community group that is a partner of this activity is the Putik Meulu Group. The group is one of the people's salt business groups, with group members consisting of inong balee (widows) whose economic life is completely deprived. This group has been running its business since 2000 and can produce around 200 kilograms of salt every day from five kitchens with assets of around Rp 23,500,000,-. The results of service activities, with a training in clean salt production and various kinds of business management, were able to change the mindset of partners related to the salt production process such as 1) the salt kitchen was made permanent, 2) it was given a fence around to avoid animals entering the salt kitchen, and 3) from the production aspect, the average salt production increased to 90 kg/day. In addition, the salt production was also white and free from impurities. In conclusion, with the training in salt clean production and various kinds of business management, it has succeeded in opening the mindset of partner salt farmers to use advanced technology to increase their salt productivity.